Mxiin7
Answered

Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

HELPS WHATS THE ANSWER

HELPS WHATS THE ANSWER class=

Sagot :

Answer:

A

Step-by-step explanation:

(f - g)(x)

= f(x) - g(x)

= 3x² + 4x - 8 - (2x - 5) ← distribute parenthesis by - 1

= 3x² + 4x - 8 - 2x + 5 ← collect like terms

= 3x² + 2x - 3 → A

Answer:

[tex]3x^2+2x-3[/tex]

Step-by-step explanation:

[tex]3x^2 - 4x - 8 - ( 2x - 5 )[/tex]

[tex]3x^2- 4x - 8 - 2x + 5[/tex]

[tex]3x^2 +4x - 8 - 2x + 5[/tex]

[tex]3x^2+2x-3[/tex]

[tex]Solution = 3x^2+2x-3[/tex]